The beauty of chemistry : art, wonder, and science - Ball, Philip, 1962- (The MIT Press, 2020)
Images and text capture the astonishing beauty of the chemical processes that create snowflakes, bubbles, flames, and other wonders of nature. Chemistry is not just about microscopic atoms doing inscrutable things; it is the process that makes flowers and galaxies. We rely on it for bread-baking, vegetable-growing, and producing the materials of daily life. In stunning images and illuminating text, this book captures chemistry as it unfolds. Using such techniques as microphotography, time-lapse photography, and infrared thermal imaging, The Beauty of Chemistry shows us how chemistry underpins the formation of snowflakes, the science of champagne, the colors of flowers, and other wonders of nature and technology. We see the marvelous configurations of chemical gardens; the amazing transformations of evaporation, distillation, and precipitation; heat made visible; and more. The visuals in The Beauty of Chemistry are drawn from the online exhibition Envisioning Chemistry created by Wenting Zhu and Yan Liang in collaboration with the Chinese Chemical Society. These striking images are accompanied by accessible, engaging explanations by award-winning science writer Philip Ball.- Resumé vydavatel